2021
DOI: 10.1155/2021/6652915
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Stem Cell (SC) Differentiation into Insulin-Producing Cells for Treating Diabetes: a Systematic Review

Abstract: Over the recent years, the use of stem cells has provided a new opportunity to treat various disorders including diabetes. Stem cells are unspecialized cells with a capacity for self-renewal and differentiation into more specialized cell types. Many factors contribute to the differentiation of SCs and thus play an important role in regulating the fate of stem cells. Accordingly, a wide range of protocols has been used to differentiate SCs to insulin-producing cells but the effectiveness of SC differentiation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Considerable progress has been achieved in devising IPCs differentiation protocols suitable for potential clinical applications. In fact, a versatile range of differentiation protocols capable of generating IPCs from various sources of stem cells are now widely available [ 34 ]. However, the differentiation efficiency and the maturation capacity of those generated cells, are still faced with challenges that need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable progress has been achieved in devising IPCs differentiation protocols suitable for potential clinical applications. In fact, a versatile range of differentiation protocols capable of generating IPCs from various sources of stem cells are now widely available [ 34 ]. However, the differentiation efficiency and the maturation capacity of those generated cells, are still faced with challenges that need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In the other in vivo studies differentiated [37,2,9,36,16,58,72,61] SCs were transplanted to patient or animals and exhibited liver regeneration, also, their liver function improved.…”
Section: Differentiationmentioning
confidence: 99%
“…Liver disorders include a wide range of both acute and chronic conditions, which are linked with remarkably morbidity and mortality across and differentiation into several specialized cell types. In vitro condition, several factors such as extracellular matrix (ECM) proteins, cell-to-cell adhesion, cell-to-cell contact, and soluble factors may affect their differentiation into specialized cell types, and play an important role in regulating the fate of stem cells [ 2 ]. Accordingly, a various range of protocols has been used to differentiate SCs toward hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…When AD-MSCs were grown in a fibroblast growth factorcontaining medium, they produced markers such as Isl1 mRNA, which are required for the formation of pancreatic islet cells 113 . Several studies have shown that AD-MSCs from the mouse epididymis can develop into cells that express PDX1, Ngn3, NeuroD, Pax4, Glut2, and produce insulin and C-peptide 114 . After 38 days of co-culture with islet cells, AD-MSCs were shown to be differentiated into iPSCs 115 .…”
Section: Adipose-derived Stromal Cells (Adscs)mentioning
confidence: 99%